Saarland's „Commercial Site Potential Model”: A method for the identification and assessment of commercial sites in spatial planning - Domhardt, Hans-Jörg; Hilligardt, Jan (Raumforschung und Raumordnung | Spatial Research and Planning, 2000)
There is a need in spatial planning for transparent and intelligible methods of assessment and decision-making to deal with a range of complex issues. With the growing need and call for coordination at regional level, more and more importance is coming to be placed, in particular, on sound methods for identifying and assessing potential commercial sites as a basis for regional planning concepts. In considering the example of Saarland's “Commercial Site Potential Model”, this article outlines the development and application of such a model and discusses the experience gained in its application within the framework of this Land-wide study, paying special attention to GIS support.
Keywords: Article